Avenue of Mysteries - Irving, John (London Doubleday, 2015)
As we grow older--most of all, in what we remember and what we dream--we live in the past. Sometimes, we live more vividly in the past than in the present. As an older man, Juan Diego will take a trip to the Philippines, but what travels with him are his dreams and memories; he is most alive in his childhood and early adolescence in Mexico. "An aura of fate had marked him," John Irving writes, of Juan Diego. "The chain of events, the links in our lives--what leads us where we're going, the courses we follow to our ends, what we don't see coming, and what we do--all this can be mysterious, or simply unseen, or even obvious." Avenue of Mysteries is the story of what happens to Juan Diego in the Philippines, where what happened to him in the past--in Mexico--collides with his future